Determination of left ventricular ejection fraction and C-reactive protein by the state of ischemic myocardium – capabilities of ECG digitalization - V. K. Tashchuk; O. V. Malinevska-Biliichuk (Zaporožskij Medicinskij Žurnal)
Aim. To determine the dependence of left ventricular ejection fraction (LVEF) and C-reactive protein (CRP) on the condition of ischemic myocardium considering additional diagnostic data, obtained from differentiated ECG.